Flexural buckling behaviour of high-chromium stainless steel welded I-section columns - Sun, Yao (2022)
The present paper reports experimental and numerical studies of the minor-axis flexural buckling behaviour and resistances of welded I-section columns made of a newly developed grade EN 1.4420 high-chromium austenitic stainless steel. The structural testing programme comprised ten pin-ended column tests as well as supplementary measurements of the initial global and local geometric imperfections of the column specimens. The structural testing programme was accompanied by a numerical modelling programme, including a validation study, where column finite element models were developed and validated against the experimental results, and a parametric study, where the validated column finite element models were employed to generate an additional numerical data bank over a broad spectrum of cross-section dimensions and member effective lengths. The obtained test and numerical data, were adopted to evaluate the applicability of the design provisions for normal stainless steel welded I-section columns, as set out in the current European code and American design guide, and cold-formed doubly symmetric section columns, as given in the existing Australian/New Zealand standard and American specification, to the new high-chromium stainless steel welded I-section columns. Overall, it was found that (i) all the four considered codes can be safely extended to cover the design of high-chromium stainless steel welded I-section columns, except for the American specification, which results in unsafe flexural buckling resistance predictions, and (ii) the most accurate and consistent design flexural buckling resistances were obtained by using the European code.